Effectiveness of the Online Election via E-Voting Based on Community Response - Harahap, Erwin; Rohaeni, Onoy; Iswani, Anneke; Syafnir, Livia; Harahap, Dedy Ansari (KnE Social Sciences, 2023)
The election of RT/RW leaders is a regular event that takes place in every village across Indonesia. Similarly, the election process was carried out at RW 23 Permata Biru housing area, located in Cinunuk Village, Cileunyi District, Bandung City Regency, West Java Province, Indonesia. The leadership of RT/RW is elected every 5 years, and in this instance, the election process occurred in November-December 2021, determining new leaders for the 2022-2027 term. However, the election faced a challenge due to the restrictions imposed by the Indonesian government related to the Covid-19 pandemic. Gathering in large groups was not permitted to curb the spread of Covid-19. Despite these circumstances, the transition of RT/RW leaders was considered crucial to avoid potential conflicts within the community. As a result, an alternative solution was implemented, conducting an online election using the E-Voting application. Through explanations and community outreach in RW 23, the people were receptive to the idea of conducting the election online, considering the ongoing Covid-19 pandemic. RW 23 comprises 732 families, divided into 10 RTs. The election process took place in two stages: first, the election of the leader of RW 23, followed by the election of the leaders of the RTs. The selection of the RW 23 leader began with the formation of a committee, followed by the dissemination of rules, candidate selection, and further outreach. The election itself was conducted through the E-Voting application. The E-Voting software was created using Google Form Apps, with the assistance of Microsoft Excel. Community members accessed the E-Voting application through their PCs and smartphones. Despite the challenges, the election of the RT/RW leaders proceeded smoothly and safely. As a result, a new team of RT/RW leaders was formed for RW 23, serving during the 2022-2027 period. Keywords: online election, leader rt/rw, pandemic, Covid-19, e-voting